Biopigment from Marine Soil Bacteria Citricoccus sp. - Ezhil, D.; Meignanalakshmi, S.; Haritha, B. (Science and Technology: Recent Updates and Future Prospects Vol. 10, 2024)
Despite the complications in the isolation of pigments from natural resources, microbial pigments are increasingly gaining the attention of researchers because of their potential to be used in the textile, cosmetics, pharmaceuticals, food industries, etc. The aim of this study is to isolate, and characterize pigmented bacteria from marine soil and optimize the culture condition for optimum pigment production. The yellow-pigmented bacteria were isolated on a nutrient agar medium and screened for motility, gram staining, and biochemical tests. The study mainly focused on using microbial pigment for dyeing cotton fabrics and woolen threads. We found out that the rate of pigment production was increased by optimizing the pH and temperature along with supplementing 1% glycerol as carbon and 0.5% beef extract as nitrogen sources. The pigment was extracted using methanol as solvent and was characterized through UV-visible spectroscopy and Fourier Transform Infrared (FTIR) spectroscopy whose values and phytochemical analysis results proved that the pigment belongs to the carotenoid group. Through 16s rRNA sequencing the bacteria was identified as Citricoccous sp.